‘Animal Farm’: the faunal record from the Chalcolithic Ota Site (Alenquer, Portugal) and its regional significance - Almeida, Nelson J. (2022)
This paper presents the results of the excavations carried out in the Chalcolithic contexts from the walled enclosure of Ota (Alenquer, Portugal). Six new absolute dates allow the discussion of the stratigraphical evidence and chronologically frame the zooarchaeological and taphonomical analysis of the faunal assemblage. Domesticated swine, caprine and bovine are prevalent, while wild species, most notably leporids, but also red deer, auroch and wild boar, among others, are less common. Exploitation and management of animals for the acquisition of primary and secondary products are inferred. Existing data suggests that the economic intensification that started during the previous phases was ongoing.